2009
DOI: 10.1007/s12161-009-9090-3
|View full text |Cite
|
Sign up to set email alerts
|

Soybean Allergens Affecting North American Patients Identified by 2D Gels and Mass Spectrometry

Abstract: In this study, we compared the immunoglobulin E immunological reactions of 23 soy-allergic, nine soysensitive, and four non-allergic human sera to soybean proteins separated by 1D and 2D gel

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 34 publications
2
16
0
1
Order By: Relevance
“…3, 5, 12, and 22) were identified as corresponding to allergenic molecules (Table 2 ). It has reported that class I small heat shock protein (Hsp) is one of allergens in soybean (Gagnon et al, 2010 ). Hsp70 proteins have been demonstrated to bind to human IgE from patients sensitized to penicillium (Shen et al, 1997 ), cystic echinococcosis (Ortona et al, 2003 ), and to corn and wheat dust (Chiung et al, 2000 ).…”
Section: Resultsmentioning
confidence: 99%
“…3, 5, 12, and 22) were identified as corresponding to allergenic molecules (Table 2 ). It has reported that class I small heat shock protein (Hsp) is one of allergens in soybean (Gagnon et al, 2010 ). Hsp70 proteins have been demonstrated to bind to human IgE from patients sensitized to penicillium (Shen et al, 1997 ), cystic echinococcosis (Ortona et al, 2003 ), and to corn and wheat dust (Chiung et al, 2000 ).…”
Section: Resultsmentioning
confidence: 99%
“…Protein extracts were obtained by centrifugation and stored at 4°C until further use. The Tris extracts were prepared by homogenising 1 g of sample in 10 mL Tris buffer (20 mM Tris pH 7.6; 150 mM NaCl; 1 mM EDTA) [34] using the same procedure as described for the urea/phosphate buffer. The same extraction procedures were applied for pink peppercorn and sumac, except that 2.5 and 5 g of sample was used per urea/phosphate or Tris buffer, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…With respect to heavy metals such as cadmium, the importance of selecting low-Cd uptake genotypes is obviously clear and indisputable when considering the accumulation effect and long half-life of Cd in the human body as a consequence of chronical intake (JÄRUP and ÅKESSON, 2009; JHA and BOHRA, 2016). In contrast, in the field of allergen removal, the prevalence of particular allergens and the clinical relevance of null-mutants such as the P34-null soybean need to be better confirmed prior to introgression of the trait; while P34 is regarded as the immunodominant allergen in most reports, other allergenic proteins are considered as more significant in some studies (GAGNON et al, 2010). Apart from the human food safety discussion, soybean allergen removal might also become relevant in livestock and aquaculture feeding, as pigs and other mammals have been described to show allergic reaction against P34 or other soybean proteins, and salmonoids are developing hypersensitivity to soy-based feeds (SEWEKOW et al, 2012;SCHMIDT et al, 2015;HERMAN and SCHMIDT, 2016).…”
Section: Discussionmentioning
confidence: 99%